Organ formation and plant regeneration in vitro tissue culture of Crassula arborescens - LIU Yong-li; LONG Zi-li; GAO Yue; Takashi Harada (浙江大学学报. 农业与生命科学版)
Effects of medium and plant growth regulators on shoot regeneration from stem, leaf and root explants of Crassula arborescens were studied. Adventitious buds developed into shoots, shoot regeneration rate reached 100% and shoot number was above 10 per explant on the Murashige and Skoog basal medium (MS) supplemented with 0.1-10 μmol·L-1 α-naphthaleneacetic acid (NAA) and 10 μmol· L-1 N-6-benzyladenine (BA). Rooted shoots grew into vigorous plantlets after transferred to 1/2 MS medium containing 1 μmol·L-1 NAA or 1 μmol·L-1 indolebutyric acid (IBA). The rooted plantlets were transplanted to the field, grew very vigorous and reached 27 cm height after 8 months.